2019
DOI: 10.3390/v11121164
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Surveillance at the Human–Animal Interface in West-Central Brazil, 2017–2018

Abstract: Zika virus (ZIKV) was first discovered in 1947 in Uganda but was not considered a public health threat until 2007 when it found to be the source of epidemic activity in Asia. Epidemic activity spread to Brazil in 2014 and continued to spread throughout the tropical and subtropical regions of the Americas. Despite ZIKV being zoonotic in origin, information about transmission, or even exposure of non-human vertebrates and mosquitoes to ZIKV in the Americas, is lacking. Accordingly, from February 2017 to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…aegypti may play a role in D. immitis transmission, which warrants further research. Prior studies have also documented the potential spill-over of human-amplified urban arboviruses into wild or domestic animals [83,84], suggesting that Ae. aegypti could play the role of a bridge vector in this context.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti may play a role in D. immitis transmission, which warrants further research. Prior studies have also documented the potential spill-over of human-amplified urban arboviruses into wild or domestic animals [83,84], suggesting that Ae. aegypti could play the role of a bridge vector in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some of these same monkey and mosquito species have been shown to be susceptible to experimental infection with ZIKV 10 13 , and ZIKV has been isolated from monkeys in suburban neighborhoods in Brazil 14 , 15 . However, the virus has not been isolated from free-living forest mosquitoes, although at present, only low-numbers of the most likely sylvatic vector species have been screened 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This frequency of positivity was much lower than we expected, as were the data of Ribeiro et al Like in their study, our data cannot be attributed to problems in the execution of PRNT 90 , since the protocol established by Baer and Kehn-Hall ( 36 ) was strictly followed. The ZIKV/H.sapiens/Brasil/ES2916/2015 strain was identified in the State of Espírito Santo at the time of the CZS epidemic in Brazil ( 68 ). In a case report, it was shown that a child was positive for ZIKV IgG at birth and at the age of 12 months but was negative at 21 and 24 months of age.…”
Section: Discussionmentioning
confidence: 99%